HISTORY OF RELATIONS BETWEEN THE UMAYYAD CALIPHATE AND THE TURKISH KHAGAN IN FOREIGN STUDIES - N. Yuldashev (Modern American Journals, 2025)
This article examines the emergence of the Türgesh, one of the tribes belonging to the On Oq (Ten Arrows) federation of the Western Turks, as a new imperial power in the Central Asian steppes at the end of the 7th and beginning of the 8th century, following the decline of the Western Ashina Turks. Although the Türgesh Khaganate existed for a relatively short period—approximately twenty years, mainly during the reign of Khagan Suluk—it played a significant role in both regional and transregional political systems during the first half of the 8th century. Under the military and diplomatic leadership of Suluk Khagan, the Türgesh consolidated their influence in the regions of Mawarannahr and Tokharistan and entered into geopolitical rivalry with major powers such as the Tang Empire, the Umayyad Caliphate, Tibet, and the Eastern Turks. Their active support for local populations resisting Umayyad expansion transformed the Türgesh into a key factor in the balance of power in the region. The article highlights how foreign scholarship reflects on the Türgesh Khaganate as a significant political entity in the historical processes of early 8th-century Central Asia.
Keywords: 6th–8th centuries CE; Chinese Empire; Eurasia; imperialism and conquest; nomads; steppes.